2020
DOI: 10.1111/ruso.12345
|View full text |Cite
|
Sign up to set email alerts
|

“Breaking Even” under Intensification? Gendered Trade‐Offs for Women Milk Marketers in Kenya*

Abstract: Despite the commonly vaunted "win-win" prospect of combining intensified livestock production with greater gender equality, the benefits of formal marketization of livestock products are generally skewed toward men. In response to this global trend, there is a growing impetus to better understand the gender dynamics underlying women's market participation to curtail the risk of worsening gender inequalities in agricultural systems transitioning to intensified production. This study analyzes the spectrum of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It is very hard because people go through short-cut routes [and sell to hawkers]. (Site C, HH1, woman) However, as some studies have shown, some local milk buyers are also women who depend on this small trade for their livelihoods [41,42]. Dairy development programs, however, often do not promote a variety of milk selling channels but privilege the large processors.…”
Section: Access To Market or Community Consumption?mentioning
confidence: 99%
“…It is very hard because people go through short-cut routes [and sell to hawkers]. (Site C, HH1, woman) However, as some studies have shown, some local milk buyers are also women who depend on this small trade for their livelihoods [41,42]. Dairy development programs, however, often do not promote a variety of milk selling channels but privilege the large processors.…”
Section: Access To Market or Community Consumption?mentioning
confidence: 99%
“…While many women's empowerment metrics perpetuates the notion that gender is merely a property of atomized individuals, who are independent of other actors, contemporary gender theory sees gender as relational (Hackfort and Burchardt 2018;Jerneck 2018;Risman et al 2018;Leslie et al 2019). Gender gains meaning through social practices that structure hierarchies of gendered power in given contexts (Tavenner et al 2020). This hierarchy is shaped by localized notions of socially desirable/acceptable masculinities and femininities (Schippers 2007) and sex disaggregated survey data does not capture how gender is mediated by societal relations and structures.…”
Section: Ignoring How Localized Gender Power Relations In Agricultural Systems Shape the Meaning Of Empowermentmentioning
confidence: 99%
“…Some of the documented pathways to realize WE through livestock production include women's livestock ownership and management; women's participation in the livestock market and the commercialization of live animals, animal products, and animal inputs; and the opportunity for women to control and make decisions over these products and over the income generated from their sale (Njuki & Sanginga, 2013). For example, women often sell surplus eggs and milk and control the generated revenues, which they can use to meet their own or their household's needs (Njuki and Sanginga, 2013;Tavenner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%